EFFECT OF ZEOLITE ON AMMONIA TOXICITY AND ON SOME OF BLOOD PARAMETERS IN COMMON CARP CYPRINUS CARPIO - & Al-Rudainy, Alaa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The current study was undertaken to investigate the efficacy of different levels of natural zeolite on ammonia and on some of blood parameters of Cyprinus carpio. The experimental treatments included adding zeolite as stones placed in the bottom of aquarium : Control( 0 zeolite); T1, T2 and T3 zeolite stones were added in the water at concentrations of 6 , 8 and 10 mg/l respectively. Results of ammonia concentrations ranged between 0.17 – 1.25 mg/l in T2 and in control treatment respectively from the first week up to fourth week. In T1 values of ammonia were 0.18mg/l in first week with gradually increase from 0.48 mg/l in second week and 0.78mg/l in the third week, then decline to 0.66mg/l in the fourth week, same condition was found in T2 and T3. In the second week level of ammonia was increased highly in control treatment , compared to other treatments. In the third week the increasing level of ammonia was continuously especially in control treatment followed by T3,T2 and T1 respectively. In the fourth week the level of ammonia recorded 1.25 mg/l , but decrease in T3 which reached 0.62mg/l. No mortalities were recorded in the first week for all treatments during the experimental period, while, in the fourth week in control reached up to 100% mortality compared with the T1,T2 and T3 which recorded 50, 33.33 and 33.33% respectively . Generally results showed that ammonia and mortality were decreased with increased zeolite level in water. Results of RBC ranged between 2.05 – 2.33 ×106/mm3 in control treatment and T3 respectively .The highest number of WBC in the control treatment which recorded 24.55 ×103/mm3 , while the lowest number was document in T2 (23.01×103/mm3) . The highest PCV(%) was registered inT3(26.50%). For Hb content the highest mean was reported in T3 (9.70g/dl). T3 can be considered as better treatment which contained zeolite in blood parameters followed by T2.